Credit constraints and agricultural productivity in developing countries: The case of East Africa - Kinuthia, Bethuel Kinyanjui (International Food Policy Research Institute, 2018)
Sustained agricultural growth is crucial for reducing hunger and poverty in East Africa, where majority of the population rely on agriculture for their livelihood. However, smallholder farmers in the region face long-standing challenges, including low labor productivity, low levels of profits, and credit constraints factors that have adverse effects on smallholders’ farm output and investment. This paper seeks to re-examine the impact of credit on agricultural productivity and the efficiency losses associated with credit constraints in East Africa. The data is based on the Living Standards Measurement Study-Integrated Surveys on Agriculture for Tanzania and Uganda. The results show that credit affects agricultural productivity in East Africa in various ways. For example, households’ decision to borrow affects agricultural productivity in Uganda but not Tanzania. Additionally, the decision to borrow from formal and semi-formal sources affects agricultural productivity, and thus efficiency, significantly and positively in Uganda compared to Tanzania.